Status of claw recordings and claw health in Danish dairy cattle from 2013 to 2017. (November 2021) - Capion, N.; Raundal, P.; Foldager, L.; Thomsen, P.T.
Highlights: Digital records of claw health were collected in 45% of Danish dairy herds. Digital dermatitis (DD) was recorded in 95% of the herds in 2017. The prevalence of DD decreased with parity. The prevalence of sole ulcer and white line abscess increased with parity. The number of claw trimming recordings increased during the 5-year period. Abstract: Since 2009, Danish claw trimmers have been able to record claw health digitally during trimming. The records are owned by the farmer and can be used locally in the herd and on a large scale by breeding organisations to improve claw health. The objective of this study was to describe data on claw recording routines and describe the prevalence of digital dermatitis (DD), interdigital hyperplasia (IH), sole ulcer (SU) and white line abscess (WLA) recorded by claw trimmers (TrimmerID) at trimming. More than 5.18 million records of cows with claw recordings and 2.75 million records of claw trimming with 2.4 million concurrent claw diseases from 62 TrimmerIDs from 705, 803 animals from 1635 herds over a 5-year period from 2013 to 2017 were included in the dataset. Data on cow level was used for the descriptive statistics. The data was restricted to, and grouped by, heifers from 12 months of age, first, second and third or older parity cows from the breeds Holstein, Danish Red Dairy, Jersey and crossbreds. The number of recorded trimmings per TrimmerID per year varied from 132 to 48, 040 with a mean of 9556 and increased during the period studied. The overall prevalence across breed and parity groups of DD, IH, SU and WLA was 21%, 6%, 7% and 3%, respectively. The prevalence of the lesions remained quite constant during the 5-year period. DD was recorded in 95% of the herds in 2017. The prevalence of IH, SU and WLA increased with increasing parity. Digital recording of claw lesions may be a good indicator of claw health. However, the recording routines and quality of the recordings must be considered.